IMPORTANCE OF SYLLABLE, ITS FORMATION AND SEPARATION ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article discusses the critical role that syllables play in language, emphasizing their importance in pronunciation, reading, and writing. It explains what syllables are, detailing their structure and function within words. The article outlines different types of syllables, such as closed, open, vowel-consonant-e, vowel team, and r-controlled syllables, highlighting how each type contributes to word formation and pronunciation. The article also examines the significance of syllable separation, or syllabification, as a tool for improving literacy skills. It presents basic rules for separating syllables, including the vowel-consonant-vowel rule, handling double consonants, and recognizing consonant-le endings. These rules are illustrated with examples, demonstrating practical applications in reading, writing, and phonics instruction. By breaking down the concepts of syllables, their formation, and separation, the article provides valuable insights for educators, students, and language learners. It underscores the necessity of syllable awareness in enhancing language proficiency, communication skills, and overall literacy development. The article serves as a resource for those interested in understanding the foundational aspects of language and the mechanics of syllable structure.